PROBLEMS IN TRANSLATING BETAWI CULTURE IN TWO STORIES FROM A BOOK ENTITLED ''DONGENG BETAWI TEMPO DULU'' BY ABDUL CHAER - WURIJ HANDAYANI (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2023)
It is difficult to translate stories that have cultural components. The story's purpose and content must be understood by the translator. Additionally, the translator needs to be culturally aware. Google Translate makes it simple for translators to translate the story's sentences, words, and phrases. But after being translated by Google Translate, certain words and phrases have different meanings. The goal of this study is to identify translation issues in words or sentences that Google Translate has translated. This study makes use of content analysis in qualitative research. The researcher discovered that translations of words referring to food and drink that incorporate aspects of Betawi culture are often inaccurate. Additionally, terms with cultural connotations like babe and munjung have not been translated according to their meaning.